Feasibility of moving a large building model from Revit to Audytor OZC - Strzeszewski, Michał; Wereszczyński, Piotr; Jędrzejewski, Mariusz (Instal, 2021)
The article discusses the use of BIM technology to perform thermal calculations of buildings in the Audytor OZC program in cooperation with the Autodesk® Revit® program. The feasibility of transferring the model from Revit to Audytor OZC in case of a large and complex building was confirmed. The encountered problems were discussed and proposed solution methods were presented.
Keywords: HVAC; BIM; Audytor; Revit